Extreme population divergence and conservation implications for the rare endangered Atlantic Forest sloth, Bradypus torquatus (Pilosa: Bradypodidae) - Lara-Ruiz, Paula; Chiarello, Adriano G.; Santos, Fabrício R. (Biological conservation, 2008)
The maned sloth (Bradypus torquatus) is an endangered species endemic to the Atlantic Forest of eastern Brazil. This biome has been reduced to 7% of its original extent and the remaining forests are highly fragmented. We analyzed 70 samples from the largest remnant populations in the states of Bahia, Espírito Santo and Rio de Janeiro to characterize their geographic structure and to produce estimates of genetic diversity. The analysis indicated that the remnant populations are reproductively isolated and extremely divergent. The populations present a very discontinuous distribution, with divergent genetic clusters specific to different geographical regions, probably caused by allopatric fragmentation. This pattern is likely related to Pleistocenic climatic and vegetation changes, and indicates the presence of at least two independent evolutionary units. The analyses also indicate that populations separated by more than 100km should be considered different management units. Thus, devastation of the Atlantic Forest leads to an unrecoverable loss of genetic diversity in this species. These conclusions should direct conservation actions aimed at preserving the distinctiveness of each evolutionary unit, as well as to preserve the demographic isolation of different management units.